New Paradigm of Social Commerce Regulation Towards Indonesia Cyber Era (Comparative Study between Malaysia and South Korea) - Yayuk Whindari; Narina Rani Nilam Pratiwi; Muchammad Zidan Taufiqi; Mustafa Lutfi; Maya Ruhtiani (Universitas Muhammadiyah Purwokerto, 2024)
AbstractThe emergence of Social Commerce in Indonesia raises the need for new, more comprehensive regulations to govern and protect this activity. Social commerce is a combination of social media and e-commerce, in various countries, especially Indonesia, has now developed very rapidly. This development creates new challenges in legal regulation, because social commerce involves various aspects that must be protected. This research discusses the development of social commerce in Indonesia and several countries and the design of regulating social commerce in Indonesia. The type of research used is normative juridical research, with statutory, comparative, and conceptual approaches. This research aims to find out the development of social commerce in various countries, especially Indonesia and design a formulation of social commerce regulation that is suitable to be applied in Indonesia. The results illustrate that Indonesia needs to improve security and add several provisions in the law regarding personal data protection and consumer protection in the realm of electronic commerce, especially in social media and form several institutions that support consumer protection and consumer personal data.Keywords: e-commerce, Malaysia, social commerce, South Korea.